ANALISIS PENGARUH RASIO LANCAR, PERPUTARAN PERSEDIAAN DAN MARGIN LABA KOTOR TERHADAP PEMILIHAN METODE PERSEDIAAN PADA PERUSAHAAN DAGANG YANG TERDAFTAR DI BEI TAHUN 2013-2015 - A Kadim (universitas Pamulang, 2019)
The purpose of This study is to analyse the influence of current ratio, inventory turnover and gross profit margin on the selection of inventory valuation method at trading companies listed in Indonesia Stock Exchange from 2013 to 2015. This research used the descriptive quantitative method within panel data (time series and cross section) as the type of data and the data were gotten from secondary data, acquired from Bursa Efek Indonesia, as the source of data. The sample in this research are trading companies listed on Indonesia Stock Exchange (IDX) from 2013 to 2015 were selected using purposive sampling method. The data were analysed by using regressive logistics technique. The results of the research show that current ration and gross profit margin affect the inventory accounting of method selection significantly. Meanwhile, inventory turnover does not affect the inventory accounting of method selection. Meanwhile, it is simultaneously indipendent variables are current ratio, inventory turnover and gross profit margin all having significant on dependent variable is inventory method selection